Comparative Analysis of Anesthesia Techniques and Circumcision Methods on Pain Outcomes in Pediatric Mass Circumcision: An Observational Study - Alifan Haqi; Ridwansyah; Catur Kurniawan; Ramdhan Nur Hidayat; Reza Armasyah Soenendar (Open Access Indonesian Journal of Medical Reviews, 2025)
Circumcision is a common procedure in Indonesia, often performed in mass settings. The associated pain can lead to significant psychological distress in children. Effective pain management is crucial but often challenging in mass circumcision events. This study aimed to identify determinants of pain intensity, specifically comparing anesthesia techniques and circumcision methods, during pediatric mass circumcision. An observational study was conducted in February 2023 involving 56 male children aged 0-10 years undergoing mass circumcision in Bandung and Cirebon, Indonesia. Data collected included anesthesia technique (needle-free injection [NFI], injection, topical + NFI), anesthetic agent (lidocaine vs. lidocaine/pehacain mix), circumcision method (guillotine with thermocautery vs. modified dorsal slit clamp with electrosurgery), presence of phimosis, and event location. Pain was assessed intraoperatively using age-appropriate scales: Neonatal/Infant Pain Scale (NIPS) for 0-<2 years, Face Legs Activity Cry Consolability (FLACC) scale for 2-7 years, and Visual Analogue Scale (VAS) for >7 years. Bivariate and multivariate linear regression analyses were performed using SPSS 20.0 to identify factors significantly correlated with pain scores. The mean age was 4.07 years (SD ± 2.75), and 78.6% had a history of phimosis. The mean pain score was 2.66 (SD ± 2.5) on relevant scales. Multivariate analysis revealed that both anesthesia technique (p=0.010) and circumcision method (p=0.000) were significantly correlated with pain scores, with a moderate overall correlation (R=0.500). Specifically, the modified clamp method was associated with significantly higher pain scores compared to the guillotine method (B=2.719). Combined topical and NFI anesthesia was associated with lower pain scores compared to other techniques (B=-1.059). In conclusion, anesthesia technique and circumcision method are significant determinants of intraoperative pain during pediatric mass circumcision. Less invasive anesthesia approaches (topical + NFI) combined with methods involving less tissue manipulation and shorter duration (guillotine with thermocautery) were associated with lower pain scores. These findings suggest that careful selection of techniques can significantly improve the pediatric experience in mass circumcision settings.